The Management of Database Administration for Accreditation of Study Programs in Islamic State Universities - Fatahillah, Ikhwan Aulia; Jubaedah, Dedah; Sutiana, Yana (IKRAITH-EKONOMIKA, 2025)
This study aims to analyze the data management processes in State Islamic Higher Education Institutions (PTKIN) to enhance their academic quality and accreditation achievements. Using a qualitative approach with case studies at several PTKINs, the research focuses on identifying challenges and proposing solutions for optimizing database management. Data collection methods include documentation, observations, and in-depth interviews with key stakeholders. The findings reveal that database management is critical for supporting accreditation and institutional development. Challenges such as insufficient human resources, system inefficiencies, and weak coordination among administrative units hinder optimal data management. However, solutions include strengthening technological infrastructure, enhancing human resource capabilities through training, and implementing integrated management information systems. Moreover, innovative technologies like artificial intelligence, big data analytics, and blockchain are recommended to improve data accuracy, security, and usability. The research concludes that effective data management significantly impacts PTKIN accreditation and reputation. Institutions need to prioritize the development of systems, policies, and resources to achieve their vision as leading educational institutions contributing to society.